A Cross-Linguistic Comprehension of Arabic and English Numerical Idioms and Proverbs - Hazaymeh, Omar; Aljawarneh, Adam (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
Proverbs and idioms are linguistic texts that were formed based on experiences which were accumulated over years and passed from one generation to another. Knowing and apprehending them enable their L2 users to understand the mentality of their native speakers. The present study aims to explore a number of Arabic and English proverbs and idioms in which numbers are used in order to comprehend the way in which they are formed and used. The corpus was subject to inspection to comprehend its linguistic structure and social functions. The findings showed that most of the Arabic and English proverbs and idioms analysed share the same number use and social function. Besides, the investigation showed that while these proverbs and idioms sometimes share the same words, others use different words in order to express the same social function.